The Effect of PDLSCs on Orthodontic Tooth Movement – A Review - Yuliati, Yuliati; Kriswandini, Indah Listiana; Halim, Olivia (Indonesian Journal of Dental Medicine, 2023)
Background: Stem cells have been widely used in various fields of the health sector, one of which is dental health. Teeth with malocclusion require orthodontic treatment to achieve good function and aesthetics. Orthodontic tooth movement (OTM) occurs due to a bone remodeling process, namely deposition in areas of tension and resorption in areas of pressure. Differentiated stem cells are thought to influence OTM through several different mechanisms. Purpose: This narrative review seeks to explain how stem cells affect the mobility of orthodontic teeth. Review(s): OTM is aided by inflammatory mediators that are produced as a result of the induction of stem cells in the periodontal ligament. These mediators control osteoclast and osteoblast differentiation and proliferation, as well as bone remodeling. Periodontal ligament stem cells (PDLSCs) are important local immune response modulators in the inflammatory milieu and have an impact on a range of immune cells. Conclusion: PDLSCs, which are included in mesenchymal stem cells (MSCs), play a role in OTM through various mechanisms that can cause acceleration in OTM.